2023
DOI: 10.1111/jcmm.17832
|View full text |Cite
|
Sign up to set email alerts
|

PSMC4 promotes prostate carcinoma progression by regulating the CBX3EGFR‐PI3K‐AKT‐mTOR pathway

Abstract: Proteasome 26S subunit ATPase 4 (PSMC4) could regulate cancer progression. However, the function of PSMC4 in prostate carcinoma (PCa) progression requires further clarification. In the study, PSMC4 and chromobox 3 (CBX3) levels were verified by TCGA data and tissue microarrays. Cell counting kit‐8, cell apoptosis, cell cycle, wound healing, transwell and xenograft tumour model assays were performed to verify biological functions of PSMC4 in PCa. RNA‐seq, PCR, western blotting and co‐IP assays were performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Mutations and expression of EGFR are associated with various types of cancers. Research has found that the downregulation of EGFR can significantly inhibit the proliferation, cell cycle, and migration of PCa cells in vitro and in vivo, and promote cell apoptosis [ 66 ]. It has been shown that using EGFR peptide-modified nanoparticles (NPs) as carriers to synergistically deliver doxorubicin (DTX) and pH-sensitive curcumin (CUR) prodrugs enables precision targeted therapy for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations and expression of EGFR are associated with various types of cancers. Research has found that the downregulation of EGFR can significantly inhibit the proliferation, cell cycle, and migration of PCa cells in vitro and in vivo, and promote cell apoptosis [ 66 ]. It has been shown that using EGFR peptide-modified nanoparticles (NPs) as carriers to synergistically deliver doxorubicin (DTX) and pH-sensitive curcumin (CUR) prodrugs enables precision targeted therapy for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted the overactivation of the PI3K/AKT [ 14 ], which is linked to poorer clinical outcomes in patients with RCC [ 15 ]. Additionally, the potential for CBX3 to influence prostate cancer growth by modulating the PI3K/AKT pathway has been suggested [ 16 ]; however, the significance of the interplay of CBX3 with the PI3K/AKT pathway in ccRCC is unclear.…”
Section: Introductionmentioning
confidence: 99%